No evidence of a genetic causal relationship between ankylosing spondylitis and iron homeostasis: A two-sample Mendelian randomization study - Yang, Mingyi; Yu, Hui; Xu, Ke; Xie, Jiale; Zheng, Haishi; Feng, Ruoyang; Wang, Jiachen; Xu, Peng (Frontiers in Nutrition, 2023)
Objective: To use a large-scale genome-wide association study (GWAS) summary data to study the genetic causal relationship between ankylosing spondylitis (AS) and iron homeostasis using mendelian randomization (MR). Methods: GWAS summary data of AS from the FinnGen consortium, and the GWAS summary data of iron homeostasis-related indicators from the UK Biobank. We screened certain single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) to explore the genetic correlation between AS and iron homeostasis (ferritin, serum iron, TIBC and TSAT) using MR. We used a random-effects variance weighted model (IVW), MR Egger, Weighted median, Simple mode, and Weighted mode to perform MR analysis, and random-effects IVW as main method. The Cochran’s Q statistic for MR-IVW analyses and Rucker’s Q statistic for MR-Egger analyses were used to detect heterogeneity. We used the MR-Egger and MR-PRESSO to detect horizontal pleiotropy. The MR-PRESSO method was also used to assess outlier SNPs. A “leave one out” analysis was performed to investigate whether the causal relationship was influenced by a SNP. We applied radial variants of the IVW and MR-Egger model for improved visualization of the causal estimate. The MR-RAPS method was used to assesses causality and validate the robustness of systemic and specific pleiotropy. Finally, we performed Maximum likelihood, Penalised weighted median, and IVW (fixed effects) to further identify the potential causal association. Results: The random-effects IVW results showed that ferritin, serum iron, TIBC, and TSAT have no genetic causal relationship with AS. The MR-IVW test and MR-Egger test also showed that there was no heterogeneity. The MR-Egger test and MR-PRESSO test showed that there was no horizontal pleiotropy. The "leave one out" analysis indicated that our MR analysis results were not driven by a SNP. The MR-RAPS analysis showed that the MR analyses were normally distributed. In addition, the MR analysis results of MR Egger, Weighted median, Simple mode, Weighted mode, MR-RAPS, Maximum likelihood, Penalised weighted median, and IVW (fixed effects) were consistent with random-effects IVW. Conclusion: Our study did not detect a genetic causal relationship between AS and iron homeostasis. Nonetheless, this does not rule out a relationship between the two at other levels.